2023
DOI: 10.3390/medicina59010124
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Retrograde Flexible Ureteroscopy and Percutaneous Nephrolithotomy for the Treatment of Renal Stones of 2–4 cm

Abstract: Background and objectives: Renal stones are widespread, with a lifetime prevalence of 10% in adults. Flexible ureteroscopy enables urologists to treat lower calyx stones or even complex renal stones through the natural orifice and achieve an acceptable stone-free rate. Hence, we analyzed the effectiveness and safety of FURS versus PCNL in treating renal stones between 20 and 40 mm in diameter. Materials and methods: We retrospectively analyzed 250 consecutive patients with large renal solitary stones (stone bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…RIRS is not recommended for stones exceeding 2 cm in diameter because it achieves worse stone clearance outcomes than does PCNL, engendering the need for staged procedures for effective treatment [ 20 ]. Another study revealed that although RIRS has proven effective in treating renal stones of 2–4 cm, it is crucial to acknowledge that multiple procedures may be necessary to address the entire stone burden completely [ 21 ]. A recent meta-analysis demonstrated that RIRS is a safe and efficient procedure for specific patients with large renal stones; nevertheless, PCNL was demonstrated to have a higher postoperative stone clearance rate than RIRS in patients with renal stones larger than 2 cm did [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…RIRS is not recommended for stones exceeding 2 cm in diameter because it achieves worse stone clearance outcomes than does PCNL, engendering the need for staged procedures for effective treatment [ 20 ]. Another study revealed that although RIRS has proven effective in treating renal stones of 2–4 cm, it is crucial to acknowledge that multiple procedures may be necessary to address the entire stone burden completely [ 21 ]. A recent meta-analysis demonstrated that RIRS is a safe and efficient procedure for specific patients with large renal stones; nevertheless, PCNL was demonstrated to have a higher postoperative stone clearance rate than RIRS in patients with renal stones larger than 2 cm did [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, older patients face a higher risk of complications related to kidney stones, and are twice as likely to require hospitalization [7, 8], which indicates there is a need to provide special attention and care to this population.Percutaneous nephrolithotomy (PCNL) is the first-line intervention for the management of complex kidney stones, and effectively can remove stones through a minimally invasive approach [9]. Compared to shockwave lithotripsy and flexible ureteroscopy, PCNL is associated with a higher success rate and stone-free rate [10][11][12]. Despite its advantages, this procedure can lead to potential complications Yaw-Jen Chang…”
mentioning
confidence: 99%
“…Percutaneous nephrolithotomy (PCNL) is the first-line intervention for the management of complex kidney stones, and effectively can remove stones through a minimally invasive approach [9]. Compared to shockwave lithotripsy and flexible ureteroscopy, PCNL is associated with a higher success rate and stone-free rate [10][11][12]. Despite its advantages, this procedure can lead to potential complications Yaw-Jen Chang…”
mentioning
confidence: 99%